Childhood-Onset Neurodegeneration with Cerebellar Atrophy Syndrome: Severe Neuronal Degeneration and Cardiomyopathy with Loss of Tubulin Deglutamylase Cytosolic Carboxypeptidase 1 - Samur, Bahadir M.; Ercan-Sencicek, Gulhan A.; Gumus, Hakan; Gumus, Gulsum; Baykan, Ali; Caglayan, Ahmet Okay; Per, Huseyin (Journal of Pediatric Neurology, 2022)
The cytoskeleton is a dynamic filamentous network with various cellular and developmental functions. The loss of cytosolic carboxypeptidase 1 (CCP1) causes neuronal death. Childhood-onset neurodegeneration with cerebellar atrophy (CONDCA, OMIM no.: 618276) is an extremely rare disease caused by ATP/GTP binding protein 1 (AGTPBP1) gene-related CCP1 dysfunction of microtubules affecting the cerebellum, spinal motor neurons, and peripheral nerves. Also, possible problems are expected in tissues where the cytoskeleton plays a dynamic role, such as cardiomyocytes. In the present study, we report a novel homozygous missense (NM_015239: c.2447A > C, p. Gln816Pro) variant in the AGTPBP1 gene that c.2447A > C variant has never been reported in a homozygous state in the Genome Aggregation (gnomAD; v2.1.1) database, identified by whole-exome sequencing in a patient with a seizure, dystonia, dilated cardiomyopathy (DCM), and accompanying atrophy of caudate nuclei, putamen, and cerebellum. Unlike other cases in the literature, we expand the phenotype associated with AGTPBP1 variants to include dysmorphic features, idiopathic DCM which could be reversed with supportive treatments, seizure patterns, and radiological findings. These findings expanded the spectrum of the AGTPBP1 gene mutations and associated possible manifestations. Our study may help establish appropriate genetic counseling and prenatal diagnosis for undiagnosed neurodegenerative patients.
Keywords: CCP1; dilated cardiomyopathy; severe neuronal degeneration; AGTPBP1; cytoskeleton